The active and the passive syndrome - Diaz-Guerrero, Rogelio (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The active syndrome and the passive syndrome are presented as explanatory constructs for the study of the effect of culture on personality and the study of cross-cultural differences. These constructs are mediated by socio-cultural premises that are, in simplest terms, culturally significant statements held by a majority of the members of a society. In order to demonstrate the use of these constructs the United States was chosen as an "active” culture and Mexico as a "passive” culture. A series of 112 statements, dichotomized on the active-passive dimension, were presented to graduate students in the two countries. The results showed 101 of the statements to have high interjudge reliability and differential face validity.